Determinasi Motivasi Hedonis dan Gaya Hidup Berbelanja terhadap Pembelian Impulsif di Platform E-Commerce Shopee - Alya Rahil; Iskandar Ali Alam (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2025)
The objective of this research is to evaluate the determination of Hedonic Motivation and Shopping Lifestyle to Impulse Buying behavior among students of the Faculty of Economics and Business at Bandar Lampung University who make purchases on the e-commerce platform Shopee, influenced by their Hedonic Shopping Motivation and Shopping Lifestyle. The analysis was conducted using multiple linear regression within a quantitative framework a sample of 90 respondents was chosen through purposive sampling to examine the intensity and direction of The results indicate that Hedonic Shopping Motivation has a strong and significant impact on Impulse Buying with consumers who shop for enjoyment being more likely to make impulse purchases. Furthermore, Shopping Lifestyle also significantly affects Impulse Buying, with a more dominant impact than Hedonic Shopping Motivation. The F-test confirms that both variables together have a significant effect on Impulse Buying. This research offers valuable insights for e-commerce and emphasizes the importance of financial literacy for both consumers and academic institutions to better control impulsive buying behaviors.